O conceito de estados fracassados nas relações internacionais: origens, definições e implicações teóricas - Monteiro, Leandro Nogueira (2007)
The concepts of state weakness and failure as used nowadays in academic debates and in political discourse have been evolving since the 1980 s. These concepts were based on the ideas proposed by Robert H. Jackson in his 1982 article with Carl Rosberg Why Africa s Weak States Persist and in his 1990 book Quasi-states. Nevertheless, it was after the end of the Cold War that conjuncture contributed to structure the concept of failed state , and to turn it into regular language in both academic and political entourages. These factors were namely the influence of liberal paradigms in the immediate post-Cold War times, and the consequent debates on sovereignty, intervention and human rights, as well as the aftermaths of the events of September 11th, 2001, with the securitisation of the failed state idea. This paper seeks, firstly, to exhibit a brief history of the use of the failed state concept in the post-Cold War era. Secondly, it seeks to present the conceptualisation of state failure such as used by the literature, throwing some light over those conceptual cores that provide unity to the diverse definitions of state failure. Thirdly, it seeks to present some implications of the development of the Failed state concept to the broader theoretical field of International Relations, especially regarding Liberalism, Realism and Post-Positivism